Utility of AD8 for Cognitive Impairment in a Chinese Physical Examination Population: A Preliminary Study - Yue Xie; Ya Gao; Jianjun Jia; Xiaohong Wang; Zhenfu Wang; Hengge Xie (The Scientific World Journal)
Objective. To investigate the utility of AD8 for cognitive impairment in a Chinese physical examination population. Methods. Military cadres who took routine physical examination in Chinese PLA General Hospital from Jan 1, 2013, to Dec 31, 2013, were subjected to AD8 scale. Individual information such as age, gender, and education was also collected. All data were analyzed by SPSS 19.0. Results. 1544 subjects were enrolled in this study with mean age 75.4 ± 10.6 years. The subjects who scored 0 to 8 of AD8 scale were 1015, 269, 120, 60, 30, 14, 19, 8, and 9, respectively. Corresponding proportions were 65.7%, 17.4%, 7.8%, 3.9%, 2.0%, 0.9%, 1.2%, 0.5%, and 0.6%, respectively. The endorsement prevalence of 8 questions was 5.6%, 9.2%, 6.6%, 9.2%, 4.8%, 4.5%, 8.9%, and 24.1%, respectively. The endorsement prevalence of question 8 was significantly higher than others (P<0.05). 260 subjects were scored equal to or greater than 2. The abnormal rate was 16.9%. All the participants were stratified into 9 groups by age; the prevalence of dementia was highly correlated with age (P<0.01). Conclusion. AD8 scale is a convenient and effective tool for cognitive screening in routine physical examination population.